Comparison of Law Between Merariq Traditional Marriage Law and Marriage Law Number 16 of 2019 - Rully Syahrul Mucharom; Wardah Yuspin; Absori (Universitas Muhammadiyah Surakarta, 2022)
Marriage Law in Indonesia is regulated in Act Number 1 of 1974 concerning Marriage and undergoing changes to Act Number 16 of 2019, which regulates how the norms and principles of marriage are considered and recognized by the Indonesian state. The purpose of marriage in Indonesia as regulated in Act Number 1 of 1974 article 1 states that: